Polymer, additive for non-aqueous electrolyte, non-aqueous electrolyte and lithium ion secondary battery

A non-aqueous electrolyte solution with a specific polymer additive addresses safety concerns in lithium-ion secondary batteries by preventing thermal runaway during short-circuits, ensuring high-Ni element ratio materials are used safely and effectively.

JP7626071B2Active Publication Date: 2025-02-04NISSAN CHEM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021551275
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-09-29
Publication Date
2025-02-04
Estimated Expiration
2040-09-29

Smart Images

  • Figure 0007626071000010
    Figure 0007626071000010
  • Figure 0007626071000001
    Figure 0007626071000001
  • Figure 0007626071000002
    Figure 0007626071000002
Patent Text Reader

Abstract

The present invention provides a polymer which contains a repeating unit represented by formula (1). (In the formula, n represents an integer of 1 or more; R1 represents an optionally substituted monovalent aliphatic hydrocarbon group having from 1 to 60 carbon atoms, an optionally substituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms or an optionally substituted monovalent heterocyclic ring-containing group having from 2 to 60 carbon atoms; L represents a single bond, an optionally substituted divalent aliphatic hydrocarbon group having from 1 to 60 carbon atoms, an optionally substituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms or an optionally substituted divalent heterocyclic ring-containing group having from 2 to 60 carbon atoms; and Ar represents an optionally substituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms or an optionally substituted divalent heterocyclic ring-containing group having from 2 to 60 carbon atoms.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer, an additive for a non-aqueous electrolyte, a non-aqueous electrolyte, and a lithium ion secondary battery. [Background technology]

[0002] In recent years, in response to the demand for smaller, lighter and more functional portable electronic devices such as smartphones, digital cameras and portable game consoles, the development of high-performance batteries has been actively promoted, and the demand for secondary batteries that can be used repeatedly by charging has increased significantly. Among them, lithium-ion secondary batteries are the secondary batteries that are currently being developed most vigorously, because they have high energy density, high voltage and no memory effect during charging and discharging. In addition, in response to recent environmental issues, the development of electric vehicles has been actively promoted, and secondary batteries as their power source are required to have higher performance.

[0003] When secondary batteries are applied to power sources for environmentally friendly vehicles such as electric vehicles and plug-in hybrid vehicles, and also to infrastructure equipment such as large-scale energy storage systems, higher reliability and safety than ever before are required in addition to improved performance. However, when the energy density and output of a battery are increased in order to improve the battery performance, it inevitably becomes easier for the battery to experience thermal runaway in situations such as abnormal heating or short circuiting, which tends to reduce safety.

[0004] A lithium ion secondary battery has a structure in which a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a separator interposed between them, are housed in a container, and the container is filled with an electrolyte (in the case of a lithium ion polymer secondary battery, a gel-like or all-solid electrolyte is used instead of a liquid electrolyte). Lithium composite oxides such as LiCoO2 are used as the positive electrode active material, and carbon materials such as graphite are used as the negative electrode active material. Such lithium ion secondary batteries are generally used with an operating voltage of 2.5 to 4.2V.

[0005] As mentioned above, the scope of application of lithium-ion secondary batteries continues to expand, and in order to further improve performance, studies are being conducted to increase the Ni element ratio in the positive electrode active material and to increase the capacity per unit mass. However, when the Ni element ratio in the positive electrode active material is increased, the temperature at which the positive electrode active material in the charged state reaches thermal runaway drops sharply and the amount of heat generated also tends to increase, making the battery more susceptible to thermal runaway in abnormal situations such as when the battery is short-circuited internally, and significantly reducing the safety of the battery.

[0006] Various attempts have been made to improve the safety of lithium ion secondary batteries against short circuits. For example, in Patent Documents 1 and 2, phosphorus-based materials are added to the electrolyte, and in Patent Documents 3 and 4, ionic liquid is added to the electrolyte to make the electrolyte flame-retardant, thereby improving the safety of the battery. However, these materials alone have low ionic conductivity and battery performance is reduced, so it is essential to use them in combination with carbonate-based solvents, which are generally used as the main solvent in lithium ion secondary batteries. Since these carbonate-based solvents are flammable, in order to make the non-aqueous electrolyte flame-retardant, it is necessary to add a large amount of phosphorus-based materials or ionic liquids, which results in worse battery performance and higher costs than when only carbonate-based solvents are used.

[0007] Therefore, in order to overcome the shortcomings of conventional organic electrolytes and additives, many attempts have been made to modify the electrode materials or develop new electrolytes containing additives. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-184870 [Patent Document 2] JP 2005-116424 A [Patent Document 3] Japanese Patent Application Publication No. 11-297355 [Patent Document 4] JP 2006-19070 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in view of the above circumstances, and has an object to provide a polymer, an additive for a non-aqueous electrolyte, a non-aqueous electrolyte, and a lithium ion secondary battery using the same, which are capable of producing a lithium ion secondary battery with improved safety in the event of a short circuit. [Means for solving the problem]

[0010] As a result of extensive research into achieving the above object, the present inventors have found that the use of a nonaqueous electrolyte solution containing a polymer having a specific structure as an additive improves the safety of a lithium ion battery during a short circuit, even when a positive electrode active material with a high Ni element ratio is used, and have completed the present invention.

[0011] That is, the present invention provides the following polymer, additive for a non-aqueous electrolyte, non-aqueous electrolyte, and lithium ion secondary battery. 1. A polymer comprising a repeating unit represented by the following formula (1): [ka] (In the formula, n is an integer of 1 or more; R 1 is Z 1 a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 is a monovalent heterocycle-containing group having 2 to 60 carbon atoms which may be substituted with L is a single bond, Z 1 a divalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 A divalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 is a divalent heterocycle-containing group having 2 to 60 carbon atoms which may be substituted with Ar is Z 2A (2+n)-valent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 is a (2+n)-valent heterocycle-containing group having 2 to 60 carbon atoms which may be substituted with Z 1 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a thiol group, a silyl group, Z 3 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 3 is a monovalent heterocycle-containing group having 2 to 60 carbon atoms which may be substituted with Z 2 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a thiol group, a silyl group, or Z 3 is a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with Z 3 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a silyl group, or a thiol group. 2. Ar is Z 2 3. A polymer of 1, wherein n is a group obtained by eliminating n hydrogen atoms from an aromatic ring of a phenylene group which may be substituted with 3. A polymer of 1 or 2, wherein L is a single bond. 4.R 1 But R 1 The polymer of any one of 1 to 3, wherein -OC(O)- is a protecting group for an amino group. 5. An additive for a non-aqueous electrolyte comprising any one of the polymers recited in 1 to 4. A non-aqueous electrolyte containing an additive for non-aqueous electrolyte 6.5. 7. The nonaqueous electrolyte of 6, wherein the content of the additive for the nonaqueous electrolyte is 0.01 to 10 mass %. 8. The nonaqueous electrolyte of 7, wherein the content of the additive for the nonaqueous electrolyte is 0.1 to 1 mass %. 9. A lithium ion secondary battery comprising the nonaqueous electrolyte according to any one of 6 to 8, and a positive electrode and a negative electrode capable of absorbing and releasing lithium. A lithium-ion secondary battery that is charged and used in the range of 10.4.0 to 5.0 V. 11. A lithium-ion secondary battery according to 9 or 10, wherein the cathode active material contained in the cathode is a lithium composite layered oxide. 12. A lithium-ion secondary battery according to 11, wherein the lithium composite layered oxide is a compound represented by the following formula (6). Li(Ni a Co b Mn c )O2(6) (In the formula, a, b, and c are numbers satisfying 0 ≦ a ≦ 1, 0 ≦ b ≦ 1, 0 ≦ c ≦ 1, and a + b + c = 1.) 13. A lithium-ion secondary battery according to 11, wherein the lithium composite layered oxide is a compound represented by the following formula (7). Li(Ni d Co e Al f )O2(7) (In the formula, d, e, and f are numbers satisfying 0 ≦ d < 1, 0 ≦ e < 1, 0 < f < 1, and d + e + f = 1.)

Advantages of the Invention

[0012] The lithium-ion secondary battery using the polymer additive of the present invention has improved safety against short circuits by using a non-aqueous electrolyte containing an additive having a specific structure even when using a cathode active material with a high Ni element ratio. Therefore, the lithium-ion secondary battery using the additive of the present invention can realize power sources for environmentally friendly vehicles such as highly safe electric vehicles and plug-in hybrid vehicles, and further infrastructure equipment such as large-scale energy storage power systems.

Brief Description of the Drawings

[0013] [Figure 1] Infrared absorption spectra of P-Boc-mPDA synthesized in Example 1, P-mPDA synthesized in Comparative Example 1, and N-(tert-butoxycarbonyl)-1,3-phenylenediamine.

Modes for Carrying Out the Invention

[0014] [polymer] The polymer of the present invention contains a repeating unit represented by the following formula (1). [ka]

[0015] In formula (1), n ​​is an integer of 1 or more, preferably an integer of 1 to 4, and more preferably 1 or 2.

[0016] In formula (1), R 1 is Z 1 a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 When n is 2 or more, each L and each R 1 may be the same as or different from each other.

[0017] Z 1 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a thiol group, a silyl group, Z 3 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 3 Z is a monovalent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with 2 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a thiol group, a silyl group, or Z 3 Z is a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 3 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a silyl group, or a thiol group.

[0018] The monovalent aliphatic hydrocarbon group is a group obtained by eliminating one hydrogen atom from an aliphatic hydrocarbon, and may be a saturated or unsaturated hydrocarbon group. In addition, these groups may be linear, branched, or cyclic.

[0019] Examples of the monovalent saturated hydrocarbon group include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, and an n-decyl group; and monovalent cyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, a bicyclobutyl group, a bicyclopentyl group, a bicyclohexyl group, a bicycloheptyl group, a bicyclooctyl group, a bicyclononyl group, and a bicyclodecyl group.

[0020] Examples of the monovalent unsaturated aliphatic hydrocarbon group include alkenyl groups such as vinyl group, 1-propenyl group, 2-propenyl group, 1-methylvinyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 2-methyl-1-propenyl group, 2-methyl-2-propenyl group, 1-ethylvinyl group, 1-methyl-1-propenyl group, 1-methyl-2-propenyl group, 1-pentenyl group, 1-decenyl group, and 1-eicosenyl group; ethynyl group, 1-propynyl group, 2-propynyl group, n-1-butenyl group, alkynyl groups such as an aryl group, a 2-butynyl group, a 3-butynyl group, a 1-methyl-2-propynyl group, a 1-pentynyl group, a 2-pentynyl group, a 3-pentynyl group, a 4-pentynyl group, a 1-methyl-3-butynyl group, a 2-methyl-3-butynyl group, a 3-methyl-1-butynyl group, a 1,1-dimethyl-2-propynyl group, a 1-hexynyl group, a 1-decynyl group, a 1-pentadecinyl group, and a 1-eicosynyl group; and monovalent cyclic unsaturated aliphatic hydrocarbon groups such as a 1-cyclohexenyl group.

[0021] The monovalent aromatic hydrocarbon group is a group obtained by eliminating one hydrogen atom from an aromatic hydrocarbon, and examples of the monovalent aromatic hydrocarbon group include an aryl group and an aralkyl group.

[0022] Examples of the aryl group include a phenyl group, a methylphenyl group, an ethylphenyl group, an n-propylphenyl group, an isopropylphenyl group, a dimethylphenyl group, a biphenylyl group, a naphthyl group, an anthryl group, and a phenanthryl group.

[0023] Examples of the aralkyl group include a benzyl group, a methylphenylmethyl group, an ethylphenylmethyl group, an n-propylphenylmethyl group, an isopropylphenylmethyl group, a butylphenylmethyl group, an isobutylphenylmethyl group, a phenylethyl group, a naphthylmethyl group, and a phenylcyclohexyl group.

[0024] The monovalent heterocyclic ring-containing group is a group obtained by removing one hydrogen atom from a heterocyclic compound. Examples of the monovalent heterocyclic ring-containing group include 2-thienyl group, 3-thienyl group, 2-furanyl group, 3-furanyl group, 2-oxazolyl group, 4-oxazolyl group, 5-oxazolyl group, 3-isoxazolyl group, 4-isoxazolyl group, 5-isoxazolyl group, 2-thiazolyl group, 4-thiazolyl group, 5-thiazolyl group, 3-isothiazolyl group, 4-isothiazolyl group, 5-isothiazolyl group, 2-imidazolyl group, 4-imidazolyl group, 2-pyridyl group, 3-pyridyl group, and 4-pyridyl group.

[0025] R 1 As for Z 1 an alkyl group having 1 to 12 carbon atoms which may be substituted with 1 a monovalent cyclic saturated hydrocarbon group having 3 to 12 carbon atoms which may be substituted with 1 an alkenyl group having 2 to 12 carbon atoms which may be substituted by 1 an alkynyl group having 2 to 12 carbon atoms which may be substituted by 2 An aralkyl group having 7 to 20 carbon atoms, which may be substituted with R, or a monovalent cyclic unsaturated aliphatic hydrocarbon group having 3 to 12 carbon atoms, which may be substituted with R, is particularly preferred. 1 As for R 1It is preferable that -OC(O)- is a group that serves as a protecting group for an amino group. For example, a tert-butyl group, an allyl group, a benzyl group, a methyl group, a 2,2,2-trichloroethyl group, a fluorenylmethyl group, a fluorenylethyl group, a 2-trimethylsilylethyl group, or the like is more preferable, and a tert-butyl group is most preferable.

[0026] In formula (1), L is a single bond, Z 1 a divalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 A divalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 Ar is a divalent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with Z. 2 A (2+n)-valent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 is a (2+n)-valent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with

[0027] The divalent aromatic hydrocarbon group represented by L is a group obtained by further eliminating one hydrogen atom from the above-mentioned monovalent aromatic hydrocarbon group, and specific examples thereof include a phenylene group, a methylphenylene group, an ethylphenylene group, an n-propylphenylene group, an isopropylphenylene group, a naphthalenediyl group, a biphenyldiyl group, a terphenyldiyl group, etc. The (2+n)-valent aromatic hydrocarbon group represented by Ar is a group obtained by further eliminating n hydrogen atoms from the above-mentioned divalent aromatic hydrocarbon group.

[0028] The divalent heterocycle-containing group represented by L is a group obtained by further eliminating one hydrogen atom from the monovalent heterocycle-containing group described above, and specific examples thereof include a thiophenediyl group, a furandiyl group, an oxazolinediyl group, an isoxazolinediyl group, a thiazolediyl group, an isothiazolediyl group, an imidazolediyl group, a pyridinediyl group, etc. The (2+n)-valent heterocycle-containing group represented by Ar is a group obtained by further eliminating n hydrogen atoms from the divalent heterocycle-containing group.

[0029] Among these, L is a single bond, Z 1 a divalent aliphatic hydrocarbon group having 1 to 20 carbon atoms which may be substituted with 2 a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms which may be substituted with Z 2 A divalent heterocyclic ring-containing group having 2 to 20 carbon atoms which may be substituted with is preferred, a single bond, Z 1 A divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms which may be substituted with is more preferred, and a single bond is even more preferred.

[0030] As for Ar, Z 2 A (2+n)-valent aromatic hydrocarbon group having 6 to 20 carbon atoms which may be substituted with Z 2 A (2+n)-valent heterocyclic ring-containing group having 2 to 20 carbon atoms which may be substituted with 2 A group obtained by eliminating n hydrogen atoms from an aromatic ring of a phenylene group which may be substituted by is even more preferred, and a group obtained by eliminating n hydrogen atoms from a phenylene group is even more preferred.

[0031] The monomer that gives the repeating unit represented by formula (1) is preferably one represented by any one of the following formulae (2) to (4). [ka]

[0032] In formulas (2) to (4), R 2 ~R 5 each independently represents a hydrogen atom, Z 1 a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with 2 a monovalent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with, a halogen atom, a hydroxy group, a nitro group, a cyano group, a boronic acid group, a sulfonic acid group, a phosphate group, a silyl group, a thiol group, -OR A , -OC(=O)-R B Or -C(=O)-OR C and R A , RB and R C are each independently 1 a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 R is a monovalent heterocyclic ring-containing group having 2 to 60 carbon atoms, which may be substituted with one of the following: 1 , L, Z 1 and Z 2 is the same as above.

[0033] Examples of the monovalent aliphatic hydrocarbon group, aromatic hydrocarbon group and heterocycle-containing group include the same as those described above.

[0034] R 2 ~R 5 Examples of the alkyl group include a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, -OR A , -OC(=O)-R B Or -C(=O)-OR C is preferred, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aralkyl group having 7 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkyloxycarbonyl group having 2 to 12 carbon atoms, or an alkylcarbonyloxy group having 7 to 12 carbon atoms is more preferred, a hydrogen atom or an alkyl group having 1 to 4 carbon atoms is even more preferred, and a hydrogen atom is most preferred. In particular, R 2 ~R 5 It is preferable that all of are hydrogen atoms.

[0035] As a monomer that provides the repeating unit represented by formula (1), one represented by the following formula (5) is also preferred. [ka]

[0036] In formula (5), R 6 ~R 14 each independently represents a hydrogen atom, an amino group, or Z 1a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 a monovalent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with, a halogen atom, a hydroxy group, a nitro group, a cyano group, a boronic acid group, a sulfonic acid group, a phosphate group, a silyl group, a thiol group, -OR A , -OC(=O)-R B Or -C(=O)-OR C where one of them is an amino group and the other is a hydrogen atom. 1 , R A , R B , R C , Z 1 and Z 2 is the same as above.

[0037] In formula (5), X is a single bond, an ester bond, an amide bond, a urethane bond, a urea bond, an ether bond, a thioether bond, -N(R D )-(wherein, R D is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms, or a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms.), a carbonate group, a carbonyl group, a sulfonyl group, Z 1 a divalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with 2 a divalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Z 2 is a divalent heterocyclic ring-containing group having 2 to 60 carbon atoms which may be substituted with

[0038] The divalent aliphatic hydrocarbon group is a group in which one hydrogen atom is further removed from the above-mentioned monovalent aliphatic hydrocarbon group, and specific examples thereof include alkanediyl groups such as methylene group, ethane-1,1-diyl group, ethane-1,2-diyl group, propane-1,2-diyl group, propane-1,3-diyl group, butane-1,4-diyl group, pentane-1,5-diyl group, and hexane-1,6-diyl group; cycloalkanediyl groups such as cyclohexane-1,1-diyl group, cyclohexane-1,2-diyl group, and cyclohexane-1,4-diyl group; alkenediyl groups such as ethene-1,1-diyl group, ethene-1,2-diyl group, and 2-butene-1,4-diyl group; and alkynediyl groups such as ethyne-1,2-diyl group. The divalent aromatic hydrocarbon group and the divalent heterocyclic ring-containing group can be the same as those described above.

[0039] R 6 ~R 14 Examples of the groups other than the amino group include a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an aralkyl group having 2 to 20 carbon atoms, -OR A , -OC(=O)-R B Or -C(=O)-OR C is preferred, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aralkyl group having 2 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkyloxycarbonyl group having 2 to 12 carbon atoms, or an alkylcarbonyloxy group having 2 to 12 carbon atoms is more preferred, a hydrogen atom or an alkyl group having 1 to 4 carbon atoms is even more preferred, and a hydrogen atom is most preferred. In particular, R 6 ~R 9 If one of the groups is an amino group, R 6 ~R 9 Preferably, one of R is a hydrogen atom. 10 ~R 13 If one of the groups is an amino group, R 10 ~R 13 It is preferable that one more of these groups is a hydrogen atom, and it is particularly preferable that all groups other than the amino group are hydrogen atoms.

[0040] In addition, X can be a single bond, an ester bond, an amide bond, a urethane bond, a urea bond, an ether bond, a thioether bond, -N(R E )-(wherein, R E is a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 6 carbon atoms, or a monovalent aromatic hydrocarbon group having 6 to 12 carbon atoms.), a carbonate group, a carbonyl group, a sulfonyl group, Z 1 a divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms which may be substituted with 2 a divalent aromatic hydrocarbon group having 6 to 12 carbon atoms which may be substituted with Z 2 A divalent heterocyclic ring-containing group having 2 to 12 carbon atoms which may be substituted with is preferred, and a single bond, an ester bond, an amide bond, a urethane bond, a urea bond, an ether bond, a thioether bond, -N(R F )-(wherein, R F is a hydrogen atom or a monovalent aliphatic hydrocarbon group having 1 to 6 carbon atoms.) A carbonate group, a carbonyl group or a sulfonyl group is more preferable, a single bond, an ether bond, a thioether bond or -NH- is even more preferable, and a single bond is most preferable.

[0041] The weight average molecular weight (Mw) of the polymer is preferably from 1,000 to 1,000,000, and more preferably from 1,000 to 100,000. In the present invention, Mw is a value measured by gel permeation chromatography (GPC) in terms of polystyrene.

[0042] [Additives for non-aqueous electrolytes] The polymer can be suitably used as an additive for a non-aqueous electrolyte solution.

[0043] [Nonaqueous electrolyte] The non-aqueous electrolyte of the present invention contains an electrolyte, a non-aqueous organic solvent, and an additive comprising the above-mentioned polymer.

[0044] The electrolyte may be any of those conventionally known for lithium ion secondary batteries. Specific examples thereof include lithium salts such as lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate, and lithium trifluoromethanesulfonate; quaternary ammonium salts such as tetramethylammonium hexafluorophosphate, tetraethylammonium hexafluorophosphate, tetrapropylammonium hexafluorophosphate, methyltriethylammonium hexafluorophosphate, tetraethylammonium tetrafluoroborate, and tetraethylammonium perchlorate; lithium imides such as lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide; and lithium borate salts such as lithium bis(oxalato)borate. The content of the electrolyte in the nonaqueous electrolyte is preferably 0.01 to 5 mol / L, more preferably 0.1 to 3 mol / L.

[0045] The non-aqueous organic solvent may be any of those conventionally known for use in lithium ion secondary batteries. Specific examples include alkylene carbonates such as propylene carbonate, ethylene carbonate, and butylene carbonate; dialkyl carbonates such as dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; nitriles such as acetonitrile; and amides such as dimethylformamide. These solvents may be used alone or in combination of two or more.

[0046] The content of the additive in the non-aqueous electrolyte is preferably 0.01 to 10% by mass, more preferably 0.1 to 1% by mass. When the content of the additive is within the above range, the non-aqueous electrolyte can be one that improves safety while not deteriorating battery characteristics. The additive may be used alone or in combination of two or more.

[0047] The non-aqueous electrolyte may further contain additives (hereinafter also referred to as other additives) conventionally known for lithium ion secondary batteries. Examples of other additives include carbonates such as vinylene carbonate, vinyl ethylene carbonate, and fluoroethylene carbonate; sulfur-containing compounds such as 1-propene-1,3-sultone; phosphoric acid esters such as trimethyl phosphate and triethyl phosphate; phosphorous acid esters such as trimethyl phosphite and triethyl phosphite; cyclic phosphazene compounds such as monoethoxypentafluorocyclotriphosphazene; aromatic compounds such as cyclohexylbenzene and biphenyl. The content of other additives is not particularly limited as long as it does not impair the effects of the present invention. The other additives may be used alone or in combination of two or more.

[0048] [Lithium-ion secondary battery] The lithium ion secondary battery of the present invention comprises the nonaqueous electrolyte, and a positive electrode and a negative electrode capable of absorbing and releasing lithium.

[0049] [Positive and negative electrodes] The positive electrode and the negative electrode (hereinafter collectively referred to as electrodes) are provided with an electrode mixture layer on a current collector. In addition, an undercoat layer may be formed between the current collector and the electrode mixture layer as necessary in order to increase the adhesion between them and to reduce the resistance at the contact interface.

[0050] The current collector may be any of those conventionally known for use in lithium ion secondary batteries. Specific examples include thin films of copper, aluminum, titanium, stainless steel, nickel, gold, silver, alloys thereof, carbon materials, metal oxides, conductive polymers, etc. The thickness of the current collector is not particularly limited, but is preferably 1 to 100 μm in the present invention.

[0051] The electrode mixture layer can be formed by applying an electrode slurry containing an active material, a binder polymer, and, if necessary, a solvent onto a current collector (or onto an undercoat layer if an undercoat layer is formed), and drying naturally or by heating.

[0052] As the active material, various active materials used in lithium ion secondary batteries can be used, for example, chalcogen compounds capable of absorbing / desorbing lithium ions or lithium ion-containing chalcogen compounds, polyanion compounds, elemental sulfur and compounds thereof, etc. can be used as the positive electrode active material.

[0053] Examples of chalcogen compounds capable of absorbing and releasing lithium ions include FeS2, TiS2, MoS2, V2O6, and V6O 13 , MnO2, etc.

[0054] Examples of lithium ion-containing chalcogen compounds include Li x Ni y M 1-y Examples of such compounds include compounds represented by the formula: LiCoO2, LiMnO2, LiMn2O4, LiMo2O4, LiV3O8, and LiNiO2 (wherein M is at least one metal element selected from Co, Mn, Ti, Cr, V, Al, Sn, Pb, and Zn, and 0.05≦x≦1.10, 0.5≦y≦1.0). Examples of such compounds include LiCoO2, LiMnO2, LiMn2O4, LiMo2O4, LiV3O8, and LiNiO2.

[0055] Examples of polyanion compounds include lithium iron phosphate (LiFePO4), etc. Examples of sulfur compounds include Li2S and rubeanic acid, etc.

[0056] Among these, the positive electrode active material is preferably a lithium ion-containing chalcogen compound, in particular a lithium composite layered oxide. As the lithium composite layered oxide, a compound represented by the following formula (6) is preferable. Li(Ni) a Co b Mn c )O2(6) (wherein, a, b, and c are numbers satisfying 0 ≦ a ≦ 1, 0 ≦ b ≦ 1, 0 ≦ c ≦ 1, and a + b + c = 1.)

[0057] Examples of the compound represented by formula (6) include LiCoO2, LiMnO2, LiNiO2, a compound where a = 1 / 3, b = 1 / 3, and c = 1 / 3 in formula (6), a compound where a = 0.5, b = 0.2, and c = 0.3 in formula (6), a compound where a = 0.6, b = 0.2, and c = 0.2 in formula (6), a compound where a = 0.8, b = 0.1, and c = 0.1 in formula (6), etc., and LiCoO2 is more preferred.

[0058] As the lithium composite layered oxide, a compound represented by the following formula (7) is also preferred. Li(Ni d Co e Al f )O2(7) (wherein, d, e, and f are numbers satisfying 0 ≦ d < 1, 0 ≦ e < 1, 0 < f < 1, and d + e + f = 1.)

[0059] As the compound represented by formula (7), a lithium composite layered oxide satisfying 0.8 ≦ d < 1, 0 ≦ e < 0.2, 0 < f ≦ 0.2, and d + e + f = 1 is preferred, and a lithium composite layered oxide satisfying 0.8 ≦ d ≦ 0.92, 0.05 ≦ e ≦ 0.17, 0.03 ≦ f ≦ 0.15, and d + e + f = 1 is more preferred.

[0060] On the other hand, as the negative electrode active material constituting the negative electrode, an alkali metal, an alkali alloy, at least one simple substance selected from the elements of Groups 4 to 15 of the periodic table that can occlude and release lithium ions, an oxide, a sulfide, a nitride, or a carbon material that can reversibly occlude and release lithium ions can be used.

[0061] Examples of the alkali metal include Li, Na, K, etc., and examples of the alkali metal alloy include Li - Al, Li - Mg, Li - Al - Ni, Na - Hg, Na - Zn, etc.

[0062] Examples of the simple substance of at least one element selected from the elements of Groups 4 to 15 of the periodic table that absorbs and releases lithium ions include silicon, tin, aluminum, zinc, and arsenic.

[0063] Similarly, examples of oxides include tin silicon oxide (SnSiO3), lithium bismuth oxide (Li3BiO4), lithium zinc oxide (Li2ZnO2), and lithium titanium oxide (Li4Ti5O 12 ), titanium oxide, etc.

[0064] Similarly, lithium iron sulfide (Li x FeS2(0≦x≦3)), lithium copper sulfide (Li x CuS (0≦x≦3) etc.

[0065] Similarly, examples of the nitride include lithium-containing transition metal nitrides, specifically Li x M y Examples include N (M=Co, Ni, Cu, 0≦x≦3, 0≦y≦0.5), lithium iron nitride (Li3FeN4), etc.

[0066] Examples of carbon materials capable of reversibly absorbing and releasing lithium ions include graphite, carbon black, coke, glassy carbon, carbon fiber, carbon nanotubes, and sintered bodies of these.

[0067] The binder polymer can be appropriately selected from known materials, and examples thereof include polyvinylidene fluoride (PVDF), polyvinylpyrrolidone, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (P(VDF-HFP)), vinylidene fluoride-chlorotrifluoroethylene copolymer (P(VDF-CTFE)), polyvinyl alcohol, polyimide, ethylene-propylene-diene terpolymer, styrene-butadiene rubber, CMC, polyacrylic acid (PAA), polyaniline, and other conductive polymers. These binder polymers may be used alone or in combination of two or more.

[0068] The amount of the binder polymer added is preferably 0.1 to 20 parts by mass, and particularly preferably 1 to 10 parts by mass, per 100 parts by mass of the active material.

[0069] As the solvent, a known solvent can be used, for example, water; ethers such as tetrahydrofuran (THF), diethyl ether, 1,2-dimethoxyethane (DME); halogenated hydrocarbons such as methylene chloride, chloroform, 1,2-dichloroethane; amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP); ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone; alcohols such as methanol, ethanol, isopropanol, n-propanol, butanol; aliphatic hydrocarbons such as n-heptane, n-hexane, cyclohexane; aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene; glycol ethers such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether; and organic solvents such as glycols such as ethylene glycol and propylene glycol. These solvents may be used alone or in combination of two or more.

[0070] An appropriate solvent may be selected from these solvents depending on the type of binder, but in the case of a water-insoluble binder such as PVDF, NMP is preferred, and in the case of a water-soluble binder such as PAA, water is preferred.

[0071] The electrode slurry may contain a conductive assistant, such as carbon black, ketjen black, acetylene black, carbon whiskers, carbon nanotubes, carbon fibers, natural graphite, artificial graphite, titanium oxide, ruthenium oxide, aluminum, and nickel.

[0072] Examples of methods for applying the electrode slurry include spin coating, dip coating, flow coating, inkjet printing, spray coating, bar coating, gravure coating, slit coating, roll coating, flexographic printing, transfer printing, brush coating, blade coating, air knife coating, etc. Among these, in terms of work efficiency, etc., dip coating, bar coating, blade coating, slit coating, roll coating, gravure coating, and flexographic printing are preferred.

[0073] The temperature at which the electrode slurry is heated and dried may also be arbitrary, but is preferably about 50 to 400°C, and more preferably about 80 to 150°C.

[0074] As the undercoat layer, a layer known for use in electrodes can be used, and for example, the layers described in International Publication No. 2016 / 194747 can be used.

[0075] The location where the electrode mixture layer is formed may be appropriately set according to the cell form of the lithium ion secondary battery used, and may be the entire surface of the current collector (or undercoat layer) or a part thereof, but when used as an electrode structure in which a metal tab and an electrode are joined by welding such as ultrasonic welding for the purpose of use in a laminate cell, it is preferable to form the electrode mixture layer by applying the electrode slurry to a part of the surface of the current collector (or undercoat layer) in order to leave a welded part. In particular, for laminate cell applications, it is preferable to form the electrode mixture layer by applying the electrode slurry to the remaining part of the current collector (or undercoat layer) except for the peripheral edge.

[0076] Considering the balance between the capacity and resistance of the battery, the thickness of the electrode mixture layer is preferably 10 to 500 μm, more preferably 10 to 300 μm, and even more preferably 20 to 100 μm.

[0077] The electrode can be pressed as necessary. A commonly used pressing method can be used, but mold pressing and roll pressing are particularly preferred. The pressing pressure in the roll pressing method is not particularly limited, but is preferably 0.2 to 3 ton / cm.

[0078] The lithium ion secondary battery of the present invention may use other components that are conventionally known, so long as it includes the above-mentioned positive electrode, negative electrode, and non-aqueous electrolyte. For example, the separator may be a cellulose-based separator or a polyolefin-based separator.

[0079] The shape of the lithium ion secondary battery of the present invention is not particularly limited, and various types of cells known in the art, such as a cylindrical type, a flat wound rectangular type, a laminated rectangular type, a coin type, a flat wound laminate type, and a laminated type, can be used.

[0080] When applied to a coin type, the above-mentioned electrode may be punched into a predetermined disk shape for use. For example, a lithium ion secondary battery can be produced by placing a predetermined number of lithium foils punched into a predetermined shape on a lid of a coin cell to which a washer and a spacer are welded, placing a separator of the same shape impregnated with an electrolyte solution on top of the lithium foils, and then stacking the electrodes from above with the electrode mixture layer facing down, placing a case and a gasket, and sealing the battery with a coin cell crimping machine.

[0081] When applied to a laminated type, an electrode structure obtained by welding a metal tab to a portion (weld portion) where the electrode mixture layer is not formed may be used. In this case, the electrode structure may be made up of one or more electrodes, but generally, multiple electrodes are used for both positive and negative electrodes. It is preferable that the multiple electrodes for forming the positive electrode are alternately stacked one by one with the multiple electrodes for forming the negative electrode, and in this case, it is preferable to interpose the above-mentioned separator between the positive electrode and the negative electrode.

[0082] The metal tab may be welded at the welded portion of the outermost electrode of the plurality of electrodes, or may be welded by sandwiching the metal tab between the welded portions of any two adjacent electrodes of the plurality of electrodes. The material of the metal tab is not particularly limited as long as it is generally used in lithium ion secondary batteries, and examples of the material include metals such as nickel, aluminum, titanium, and copper; and alloys such as stainless steel, nickel alloys, aluminum alloys, titanium alloys, and copper alloys. Among these, in consideration of welding efficiency, it is preferable to use at least one metal selected from aluminum, copper, and nickel. The shape of the metal tab is preferably a foil, and its thickness is preferably about 0.05 to 1 mm.

[0083] The welding method may be a known method used for welding metals together, specific examples of which include TIG welding, spot welding, laser welding, ultrasonic welding, etc., but it is preferable to join the electrode and the metal tab by ultrasonic welding.

[0084] Examples of ultrasonic welding methods include a method in which multiple electrodes are placed between an anvil and a horn, a metal tab is placed at the weld, and ultrasonic waves are applied to weld them all at once, and a method in which the electrodes are first welded together and then the metal tab is welded.

[0085] In the present invention, in either method, not only are the metal tabs and the electrodes welded at the welded portion, but also the electrodes are ultrasonically welded to each other. The pressure, frequency, output, processing time, etc. during welding are not particularly limited, and may be appropriately set in consideration of the materials used, etc.

[0086] The electrode structure produced as described above is housed in a laminate pack, the above-mentioned electrolyte solution is injected, and the pack is heat-sealed to obtain a laminate cell. EXAMPLES

[0087] The present invention will be described in more detail below with reference to Synthesis Examples, Examples and Comparative Examples, but the present invention is not limited to the following Examples. The measuring instruments used in the synthesis examples are as follows. [GPC] Equipment: EcoSEC HLC-8320GPC (Tosoh Corporation) Column: TSK-GEL Super AW3000+AW4000 (Tosoh Corporation) Column temperature: 40℃ Solvent: 10mM LiBr / DMAc Detector: UV (271 nm) Calibration curve: Standard polystyrene [FT-IR] Equipment: IRPrestige 21 (Shimadzu Corporation)

[0088] [Example 1] Synthesis of P-Boc-mPDA [ka]

[0089] N-(tert-butoxycarbonyl)-1,3-phenylenediamine (Tokyo Chemical Industry Co., Ltd.) (4.17 g, 20 mmol), hydrochloric acid (5 mol / L, Kanto Chemical Co., Ltd.) (4 mL, 20 mmol) and pure water (96 mL) were mixed in a flask. After heating to 50°C, ammonium persulfate (Junsei Chemical Co., Ltd.) (4.56 g, 20 mmol) dissolved in pure water (100 mL) was added dropwise. After the addition, the mixture was stirred at 50°C for 4 hours. After cooling to room temperature, the precipitated polymer was filtered, washed with pure water, and vacuum dried to obtain P-Boc-mPDA (yield 1.57 g, 39%) as a brown solid. As a result of GPC measurement, Mw was 12,800 and Mw / Mn was 6.6.

[0090] [Comparative Example 1] Synthesis of P-mPDA [ka]

[0091] 1,3-phenylenediamine (Tokyo Chemical Industry Co., Ltd.) (216 mg, 2.0 mmol), hydrochloric acid (5 mol / L, Kanto Chemical Co., Ltd.) (0.4 mL, 2.0 mmol), and pure water (9.6 mL) were mixed in a flask. Ammonium persulfate (Junsei Chemical Co., Ltd.) (456 mg, 2.0 mmol) dissolved in pure water (10 mL) was added dropwise at room temperature. After the addition, the mixture was stirred at room temperature for 4 hours. The precipitated polymer was filtered, washed with pure water, and vacuum dried to obtain P-mPDA (yield 80.9 mg, 37%) as a brown solid.

[0092] [IR measurement] The infrared absorption spectra of the obtained P-Boc-mPDA, P-mPDA, and N-(tert-butoxycarbonyl)-1,3-phenylenediamine, the raw material of P-Boc-mPDA, were measured and the results are shown in Figure 1. P-mPDA has a 1700 cm -1 On the other hand, P-Boc-mPDA had no absorption around 1700 cm due to the tert-butoxycarbonyl group. -1The absorption derived from the monomer, N-(tert-butoxycarbonyl)-1,3-phenylenediamine, was clearly observed.

[0093] [Example 2] LiPF6 was dissolved in a carbonate mixed solvent (ethylene carbonate:ethyl methyl carbonate = 1:3 (volume ratio)) to a solution at 1 mol / L. Vinylene carbonate was added to the solution at 2 mass %. Furthermore, 0.72 mass % of P-Boc-mPDA synthesized in Example 1 was added as an additive to prepare a nonaqueous electrolyte solution.

[0094] Cathode active material (Li(Ni) 0.85 Co 0.10 Al 0.05 100 parts by mass of 1,02-dimethylformamide (DMF), 2 parts by mass of conductive agent (acetylene black, Denka Black powder, Denka Co., Ltd.), 2 parts by mass of conductive material (graphite powder, J-SP, Nippon Graphite Industries Co., Ltd.), 50 parts by mass of binder (PVDF, #7208 (8% by mass NMP solution), Kureha Co., Ltd.), and 15.4 parts by mass of NMP (Mitsubishi Chemical Co., Ltd.) were mixed to prepare a paste-like positive electrode composite slurry. Next, the positive electrode composite slurry was uniformly applied to both sides of a positive electrode current collector (aluminum foil, 20 μm thick, UACJ Foil Co., Ltd.) using a coating device, dried, and finally compressed using a roll press machine to obtain a one-sided composite weight of 16.4 mg / cm. 2 A positive electrode having a thickness of 55 μm on one side was produced.

[0095] A paste-like negative electrode composite slurry was prepared by mixing 100 parts by mass of a negative electrode active material (graphite, MAG-E, manufactured by Hitachi Chemical Co., Ltd.), 1.1 parts by mass of a thickener (CMC, product number 2200, manufactured by Daicel FineChem Co., Ltd.), 3.1 parts by mass of a binder (SBR, TRD2001 (48.5 mass% aqueous dispersion), manufactured by JSR Co., Ltd.), and 131 parts by mass of pure water. The negative electrode composite slurry was then uniformly applied to both sides of a negative electrode current collector (copper foil, thickness 16.5 μm, manufactured by UACJ Foil Co., Ltd.) using a coating device, dried, and finally compressed using a roll press machine to obtain a one-sided composite weight of 12.5 mg / cm. 2 A negative electrode having a thickness of 96 μm on one side was produced.

[0096] A lead portion was formed by welding an aluminum positive electrode tab to the exposed part of the aluminum foil of the positive electrode, and a nickel negative electrode tab to the exposed part of the copper foil of the negative electrode, and the lead portions were stacked with a separator (thickness 25 μm, manufactured by Asahi Kasei Corporation) interposed therebetween, and wound into a spiral shape to produce a wound electrode body. The wound electrode body was further crushed and molded into a flat shape to obtain a flat-type wound electrode body. The flat-type wound electrode body was stored in an exterior body made of an aluminum laminate film (EL408PH, manufactured by Dai Nippon Printing Co., Ltd.), and the nonaqueous electrolyte was injected so as to be 130 volume % relative to the pore volume of the positive and negative electrodes and the separator, and then sealed to produce a flat-type lithium ion secondary battery B1. The capacity of this battery at an operating voltage of 3 to 4.2 V was 912 mAh.

[0097] [Comparative Example 2] A flat lithium ion secondary battery B2 was produced in the same manner as in Example 1, except that P-Boc-mPDA was not used.

[0098] [Comparative Example 3] A flat-type lithium ion secondary battery B3 was produced in the same manner as in Example 1, except that N-(tert-butoxycarbonyl)-1,3-phenylenediamine was used as the additive instead of P-Boc-mPDA.

[0099] [Discharge rate test] The flat lithium ion secondary batteries B1 to B3 were charged and discharged under the following conditions, and the discharge capacity at each discharge rate was measured. The test results are shown in Table 1. Temperature: 25℃ Voltage: 3.0-4.2V Charging current: 1 / 3C (1C=900mA) Discharge current: 1 / 3C, 1 / 2C, 1C, 2C, 3C, 5C

[0100] [Table 1]

[0101] As shown in Table 1, the battery containing N-(tert-butoxycarbonyl)-1,3-phenylenediamine as an additive had a decreased discharge capacity, especially at high rates, compared to the battery of Comparative Example 1 using a nonaqueous electrolyte containing no additive. In contrast, the battery of Example 2 containing P-Boc-mPDA synthesized in Example 1 as an additive maintained or improved the discharge capacity, especially at high rates, compared to Comparative Example 2.

[0102] [Short circuit test] The batteries B1 to B3 thus prepared were charged at a constant current and constant voltage of 4.1 V from 300 mA (a rate equivalent to 1 / 3 C) to 30 mA (a rate equivalent to 1 / 30 C) to prepare short circuit test samples. A thermocouple for monitoring the battery temperature was installed in the center of the short circuit test sample. A zirconia ball with a diameter of 10 mm was lowered from above into the center of the short circuit test sample on the opposite side to the surface where the thermocouple was installed at a speed of 0.1 mm / sec while monitoring the battery voltage, and the center of the battery was pressed. When the battery voltage became 1 / 3 or less before the start of the test, it was considered that a short circuit had occurred, and the descent of the zirconia ball was stopped. In this test, it was determined that the battery was unsafe if the battery temperature rose to 400°C or higher and smoke was emitted from the battery, and that it was safe if the battery temperature remained below 110°C and no smoke was observed from the battery. The test results for the short circuit test samples, which were each tested three times, are shown in Table 2.

[0103] [Table 2]

[0104] As shown in Table 1, in the battery of Comparative Example 2 using a non-aqueous electrolyte containing no additive, the temperature of the battery rose to 512°C after short circuiting in all three out of three trials, and intense smoke was generated. In addition, in the battery of Comparative Example 3 using a non-aqueous electrolyte containing N-(tert-butoxycarbonyl)-1,3-phenylenediamine as an additive, the temperature of the battery rose to 512°C after short circuiting in all three out of three trials, and intense smoke was generated. In contrast, in the battery of Example 2 using a non-aqueous electrolyte containing P-Boc-mPDA as an additive, the increase in the battery temperature after short circuiting was suppressed to 110°C or less in one out of three trials with a small amount of additive of 0.72 mass%, and no smoke was generated, and an effect of improving safety during short circuiting was obtained.

Claims

1. A polymer comprising a repeating unit represented by the following formula (1): 【Chemistry 1】 (Wherein, n is an integer of 1 or more; R 1 is a group in which R 1 --O--C(O)-- serves as a protecting group for an amino group; L is a single bond or Z 2 is a divalent aromatic hydrocarbon group having 6 to 60 carbon atoms which may be substituted with Ar is a group obtained by eliminating n hydrogen atoms from an aromatic ring of a phenylene group which may be substituted by Z 2 ; Z 2 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a thiol group, a silyl group, or Z 3 is a monovalent aliphatic hydrocarbon group having 1 to 60 carbon atoms which may be substituted with Z 3 is a halogen atom, an amino group, a hydroxy group, a nitro group, a cyano group, an oxo group, a carboxy group, a sulfo group, a phosphate group, a silyl group, or a thiol group.

2. 2. The polymer according to claim 1, wherein Ar is a group obtained by eliminating n hydrogen atoms from a phenylene group.

3. 3. The polymer according to claim 1, wherein L is a single bond.

4. R 1 The polymer according to any one of claims 1 to 3, wherein is a tert-butyl group, an allyl group, a benzyl group, a methyl group, a 2,2,2-trichloroethyl group, a fluorenylmethyl group, a fluorenylethyl group or a 2-trimethylsilylethyl group.

5. An additive for a non-aqueous electrolyte comprising the polymer according to any one of claims 1 to 4.

6. A non-aqueous electrolyte comprising the additive for non-aqueous electrolytes according to claim 5.

7. 7. The non-aqueous electrolyte according to claim 6, wherein the content of the additive for the non-aqueous electrolyte is 0.01 to 10 mass %.

8. 8. The non-aqueous electrolyte according to claim 7, wherein the content of the additive for the non-aqueous electrolyte is 0.1 to 1 mass %.

9. A lithium ion secondary battery comprising the nonaqueous electrolyte according to any one of claims 6 to 8, and a positive electrode and a negative electrode capable of absorbing and releasing lithium.

10. 10. The lithium ion secondary battery according to claim 9, which is charged and used within the range of 4.0 to 5.0 V.

11. 11. The lithium ion secondary battery in accordance with claim 9, wherein the positive electrode active material contained in the positive electrode is a lithium composite layered oxide.

12. The lithium ion secondary battery according to claim 11, wherein the lithium composite layered oxide is a compound represented by the following formula (6): Li(Ni a Co b Mn c ) 2 (6) (In the formula, a, b, and c are numbers that satisfy 0≦a≦1, 0≦b≦1, 0≦c≦1, and a+b+c=1.)

13. The lithium ion secondary battery according to claim 11, wherein the lithium composite layered oxide is a compound represented by the following formula (7): Li(Ni d Co e Al f ) 2 (7) (In the formula, d, e, and f are numbers that satisfy 0≦d<1, 0≦e<1, 0<f<1, and d+e+f=1.)

Citation Information

Patent Citations

  • Secondary cell

    JP1986183870A

  • Fire-resistant electrolyte for lithium battery

    JP1992184870A

  • Sulfonated polyaniline salt composition, method of preparation and use

    JP1993503953A

  • Cold molten salt

    JP1999297355A

  • Conductive polymer substituted with acid-labile functional group to improve electrical conductivity and patterning, and composition comprising the same

    JP2004529233A